Teachers' Perceptions of Their Professional Development and the Design of Continuing Education Programs in ELT - Arias, Fabricio Chavarría (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines the perceptions and expectations of English Department faculty at the Universidad de Oriente regarding their professional development and willingness to engage in a continuing education program. Adopting a qualitative, exploratory approach, the research employed multiple instruments, including a questionnaire, a needs analysis, a SMART goals form, and semi-structured interviews with 19 teachers. The findings reveal a strong commitment to continuous improvement and a pronounced interest in obtaining international certifications in TESOL. Participants expressed preferences for virtual courses and face-to-face workshops, emphasizing the value of collaborative work and the integration of technological tools in teaching. Key barriers identified include limited institutional time and resources. The study offers practical insights for the design of contextualized, relevant, and sustainable teacher training programs aligned with institutional strategies and international standards.